Retention of Urine After Radical Hysterectomy for Cervical Cancer - Rana, Jyoti; Rong, Shi Hui; Mehata, Suersh (Health Prospect, 2018)
Background: Radical hysterectomy is the main treatment for cervical cancer. But must of the patients suffered from postoperative bladder dysfunction, such as retention of urine. Objective: To evaluate the retention of urine after radical hysterectomy for cervical cancer in the patients up to stages IA to IIB. Methodology: A cross sectional control study was conducted in the patients diagnosed with cervical cancer and treated with radical hysterectomy in the department of obstetrics and gynecology, first affiliated hospital, Zhengzhou University, P. R. of China to evaluate the postoperative retention of urine in 90 patients from 2003 to 2006. Result and Conclusion: A total of 90 patients with cervical cancer, who underwent radical hysterectomy were included in this study. 25 patients, i.e. 27.8% were menopausal and 11 patients, i.e. 12.2% had blood loss more than 500ml. The patients with retention of urine after radical hysterectomy was compared in relation with loss of blood volume intra- operatively, parity, and menopause; as the possible causes of retention of urine. The overall frequency of retention of urine among the patients who underwent radical hysterectomy for the cervical cancer was 42.2%. The statistical analysis showed that the relation of urine after radical hysterectomy for cervical cancer with loss of blood volume, parity and menopause was found to be nonsignificant. So, retention of urine after radical hysterectomy for cervical cancer might be related to the operative procedure which effects partial sympathetic and parasympathetic denervation during a radical dissection. DOI: http://dx.doi.org/10.3126/hprospect.v10i0.5636 Health Prospect Vol.10 2011, pp.1-4